Rancang Bangun Uji Ventilator Berbasis Arduino - Suriansjah Suriansjah; Taswanda Taryo (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Since the first time, coronavirus appeared in China at the ends December 2019 as known as SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2), has spread globally, the ventilators needs have increased drastically and sharply, so WHO encourages every country in the world of medicine to manufacturing and developing ventilators, especially emergency ventilators. The government instructed the Indonesian Ministry of Health through the Balai Pengamanan Fasilitas Kesehatan Jakarta which is to test the ventilator. Gas Flow Analyzer is a calibrator tool that has functions to test the ventilator. This ventilator calibrator is a product from abroad which is very expensive. In this study, a ventilator test device using an ATMEL SAM3X8E microcontroller based on Arduino was designed for process data from the incoming air pressure and flow, so that it can be displayed on the LCD and computer. From the results of data analysis based on the Mandatory Rapidly Manufactured Ventilator System (RMVS) [15], a setting with 400 mL Tidal Volume (TV), 15 BPM Breath Rate (RR), and 1 : 2 is I: E Ratio for the percentage obtained of Tidal Volume (TV) 2.7%, Minute Volume (MV) the percentage of 2.9%, Breath Rate (RR) the percentage of 1.2%, I: E ratio the percentage of 2.3%, Inspiratory Time (Ti) the percentage of 3,9%, Expiratory Time (Te) the percentage of 3.1%, Peak Inspiratory Pressure (PIP) the percentage of 13.2%, Positive End Expiratory Pressure (PEEP) the percentage of 84.3%, Peak Inspiratory Flow (PIF) the percentage of 5,3% and Peak Expiratory Flow (PEF) the percentage of 11.4%. Keywords: Calibrator, Arduino, accuracy.